Creation without restraint promoting liberty and rivalry in innovation - Bohannan, Christina; Hovenkamp, Herbert, 1948- (Oxford : Oxford University Press, 2012)
This title analyzes the current state of competition (antitrust) and intellectual property laws, and proposes realistic reforms that will encourage innovation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Intellectual property -- United States; Technological innovations -- Law and legislation -- United States